Determination of Optimum Extraction Conditions for Antioxidant Capacity from White Turmeric Rhizome (Curcuma zedoaria (Christm.) Roscoe) Using Response Surface Methodology - Nurjannah El Firsti; Yefrida; Refilda (Universitas Andalas, 2026)
The role of free radicals in oxidative stress poses risks to cells and tissues. The effect of stress and tissue oxidation damage leads to loss of structure and, ultimately, tissue necrosis. Antioxidants quell free radicals and stabilize them. White turmeric (Curcuma zedoaria (Christm.) Roscoe) rhizome, another natural source used in traditional medicine, is said to have some potential as an antioxidant. The current study sought to investigate methods used in devising the optimization of antioxidant extraction from white turmeric using the decoction method. The main factors considered were temperature, extraction time, and sample-to-solvent ratio. The DPPH assay measured at 522 nm provided the readings for antioxidant activity. The initial OFAT approach used to devise the experiment tested and confirmed those optimal conditions of extraction (80 ˚C, 50 minutes, and 1:25 g/mL). These optimal conditions were tested in the central composite design within RSM. The confirmation of optimal conditions within RSM was (84 ˚C, 51 minutes, 1:25 g/mL). The extraction of 1.3963 mg AAE/g FW and the predicted value of 1.3450 mg AAE/g FW. These findings validate the extraction efficiency in RSM and demonstrate the antioxidant potential of white turmeric in the pharmaceutical industry.